Plotting disability in the nineteenth-century novel - Walker Gore, Clare (Edinburgh University Press, 2020)
This book takes an exciting new approach to characterisation and plot in the Victorian novel, examining the vital narrative work performed by disabled characters.
Keywords: English fiction -- 19th century -- History and criticism.; People with disabilities in literature.; Disabilities in literature.; Roman anglais -- 19e siècle -- Histoire et critique.; Handicap dans la littérature.; Disabilities in literature; English fiction; People with disabilities in literature; Behinderung -- Motiv; Englisch; Roman; Behinderter -- Motiv.; Großbritannien; 1800-1899; Criticism, interpretation, etc.